2019
DOI: 10.7554/elife.41608
|View full text |Cite
|
Sign up to set email alerts
|

In-depth human plasma proteome analysis captures tissue proteins and transfer of protein variants across the placenta

Abstract: Here, we present a method for in-depth human plasma proteome analysis based on high-resolution isoelectric focusing HiRIEF LC-MS/MS, demonstrating high proteome coverage, reproducibility and the potential for liquid biopsy protein profiling. By integrating genomic sequence information to the MS-based plasma proteome analysis, we enable detection of single amino acid variants and for the first time demonstrate transfer of multiple protein variants between mother and fetus across the placenta. We further show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 52 publications
2
77
0
Order By: Relevance
“…This is especially important when considering early disease detection is critical for children, especially when trying to limit both short-and longterm sequelae of any disease. Additionally, a recent proteogenomic study revealed that newborns have three times the number of unique proteins as their mothers, further suggesting that differences in plasma proteomes between adults and children could lead to novel biological outcomes 37 . Studies focusing on sick children are critical for understanding underlying population-specific pathophysiologies and may help reduce guesswork in medical interventions currently associated with drug dosage and predicted patient response.…”
Section: Cohort Selection -Age (Adult Vs Pediatric)mentioning
confidence: 99%
“…This is especially important when considering early disease detection is critical for children, especially when trying to limit both short-and longterm sequelae of any disease. Additionally, a recent proteogenomic study revealed that newborns have three times the number of unique proteins as their mothers, further suggesting that differences in plasma proteomes between adults and children could lead to novel biological outcomes 37 . Studies focusing on sick children are critical for understanding underlying population-specific pathophysiologies and may help reduce guesswork in medical interventions currently associated with drug dosage and predicted patient response.…”
Section: Cohort Selection -Age (Adult Vs Pediatric)mentioning
confidence: 99%
“…Application of S‐Trap, SP3 and PAC in serum proteomics could be useful to improve the availability of low‐abundance proteins. With regard to protein discovery in human plasma, resolving proteins by high‐resolution isoelectric focusing coupled to mass spectrometry (HiRIEF LC/MS/MS) successfully identified more than 1500 proteins …”
Section: Resultsmentioning
confidence: 99%
“…Seven proteins constitute 85% of the total protein mass in plasma. 87 Peptides from abundant proteins crowd the spectra, hindering comprehensive profiling of the plasma proteome and making in-depth analysis of plasma cohorts challenging. Plasma depletion strategies are available, 88 but the high cost and time-consuming nature of these methods makes them unlikely to be applicable in large cohorts.…”
Section: Potential Application Of Nanomedicine Strategies For Diagnosmentioning
confidence: 99%